ANALYSIS ON STRENGTH FOR THE MILL PRESSURE SCREW PAIRS BASED ON THERMAL-STRUCTURAL COUPLING - LIU YongFeng; ZHAO ChunJiang; ZHOU Yan; GAO Xin (Jixie qiangdu)
The three-dimensional model of the pressure screw pairs is established based on the finite element software ANSYS,the bearing characteristic of the pressure screw pairs structure is calculated at room temperature. By extracting the maximum value of each fastening screw tooth root of equivalent stress,verify the mill pressure screw pairs under equivalent stress distribution is in a U shape rules. The indirect coupling method was used for calculating the bearing characteristic of the pressure screw pairs are under thermal-structure coupling at 60℃ 、100℃ temperature. Comparison of equivalent stress of screw tooth and contact pressure of screw tooth surface under different temperature. The results show that the maximum contact pressure and equivalent stress occurred in the first fastening screw tooth,and when the temperature is at 100 ℃,the maximum equivalent stress of the nut is close to yield limit of the nut material.